2015
DOI: 10.1118/1.4919680
|View full text |Cite
|
Sign up to set email alerts
|

Total variation minimization filter for DBT imaging

Abstract: An optimized digital filter for TV minimization in DBT imaging has been presented. The reliability of a logarithmic relation found between σB and λ values was confirmed and can be used in future work. Both quantitative and qualitative analyses performed in a clinical DBT image confirmed the relevance of this approach in improving image quality in DBT imaging. The results obtained are very encouraging about increasing SDNR in a short time and preserving the principal variations in image, the structures' boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…was solved in this work using the backward‐forward splitting method together with variable splitting methods to convert the 2D TV denoising problem into a denoising problem with a generalized shrinkage operator as a solution. However, there are many other ways to solve the same optimization problem including other strategies to leverage the elegance of a variety of other variable splitting method and corresponding ADMM update strategies or to incorporate the benefits of TV regularization …”
Section: Discussionmentioning
confidence: 99%
“…was solved in this work using the backward‐forward splitting method together with variable splitting methods to convert the 2D TV denoising problem into a denoising problem with a generalized shrinkage operator as a solution. However, there are many other ways to solve the same optimization problem including other strategies to leverage the elegance of a variety of other variable splitting method and corresponding ADMM update strategies or to incorporate the benefits of TV regularization …”
Section: Discussionmentioning
confidence: 99%
“…In that plane, a region of interest (ROI) containing the 0.5 mm disk and some background (BG) was extracted. To reduce the noise variation, a TV minimization filter was applied to this region [33]. In order to achieve the minimum value of TV, several values of Lagrange parameter were applied to the longitudinal direction.…”
Section: B Psf Estimation In Z-directionmentioning
confidence: 99%
“…TV is a quantity that characterizes how smoothly the intensity of an image is changing and it increases significantly in the presence of noise. Studies applying TV minimization to DBT data have grown significantly [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the IR algorithm, a certain objective function containing the data fidelity term and the regularization term needs to be well‐designed and optimized. It has been demonstrated that the regularizers such as the total variation (TV), 10 total p variation (TpV), 11 selective‐diffusion regularization, 12 curvelet sparse regularization, 13 can be used to reduce the DBT image artifacts.…”
Section: Introductionmentioning
confidence: 99%